2022
DOI: 10.1111/cas.15505
|View full text |Cite
|
Sign up to set email alerts
|

Transfer RNA‐derived fragment 5′tRF‐Gly promotes the development of hepatocellular carcinoma by direct targeting of carcinoembryonic antigen‐related cell adhesion molecule 1

Abstract: Transfer RNA‐derived fragments are a group of small noncoding single‐stranded RNA that play essential roles in multiple diseases. However, their biological functions in carcinogenesis are not well understood. In this study, 5′tRF‐Gly was found to have significantly high expression in hepatocellular carcinoma (HCC), and the upregulation of 5′tRF‐Gly was positively correlated with tumor size and tumor metastasis. Overexpression of 5′tRF‐Gly induced increased growth rate and metastasis in HCC cells in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…For example, tRF-17 binds THBS1 (Thrombospondin-1) and reduction in THBS1 expression rescue the effects of tRF-17 inhibition on breast cancer cell viability, invasion and migration [ 33 ]. Besides, adhesion molecule 1 (CEACAM1) as a direct target of 5'tRF-Gly was downregulated in Hepatocellular Carcinoma (HCC) and affected 5'tRF-Gly-mediated promotion of HCC cells [ 34 ]. To determine which genes tRF-5022B could be aiming after, we consulted a database.…”
Section: Discussionmentioning
confidence: 99%
“…For example, tRF-17 binds THBS1 (Thrombospondin-1) and reduction in THBS1 expression rescue the effects of tRF-17 inhibition on breast cancer cell viability, invasion and migration [ 33 ]. Besides, adhesion molecule 1 (CEACAM1) as a direct target of 5'tRF-Gly was downregulated in Hepatocellular Carcinoma (HCC) and affected 5'tRF-Gly-mediated promotion of HCC cells [ 34 ]. To determine which genes tRF-5022B could be aiming after, we consulted a database.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Gly-tRF can directly target the Nedd4 family-interacting protein 2 (NDFIP2), which is a component of the AKT signalling pathway, leading to migration and EMT [ 92 ]. Another study discovered that 5’tRF-Gly can bind and silence the expression of carcinoembryonic antigen-related cell adhesion molecule 1 ( CEACAM1 ), and then promote the proliferation, migration, and invasion of hepatobiliary cancer cells [ 93 ]. Analysis revealed ts-N102 may inhibit the expression of hs-mir-215 and act as a proto-oncogene in liver cancers.…”
Section: Tsrnas In Digestive System Diseasesmentioning
confidence: 99%
“…5'tRF-Gly is upregulated in hepatobiliary cancer tissues and cells, and positively correlates with tumor growth, distant metastasis, and poor differentiation. Individuals who expressed more 5'tRF-Gly had shorter survival times [ 93 ]. ts-N102 was found to be upregulated in hepatobiliary cancer tissues, while ts-N7, ts-N94, ts-N84, and ts-N37 were down-regulated.…”
Section: Tsrnas In Digestive System Diseasesmentioning
confidence: 99%
“…In addition to being a valuable noninvasive biomarker, tsRNAs could play diverse biological roles through different mechanisms including gene silencing, protein-binding abilities, ribosome biogenesis, RNA processing, and oncogenic formation, and are associated with proliferation, migration, and invasion in some types of cancer [ 8 , [15] , [16] , [17] , [18] , [19] ]. For example, Kay et al demonstrated that inhibition of 3′tsRNA-LeuCAG, which binds at least two ribosomal protein mRNAs, induces apoptosis both in vitro and in patient-derived orthotopic hepatocellular carcinoma model in mice [ 15 ].…”
Section: Introductionmentioning
confidence: 99%